Phosphate removal by Ion exchange in batch mode - T. E. Bektaş (IWA Publishing, 2021)
Water with phosphate concentrations above 2 μM may adversely affect aquatic life and human health. In this study, the parameters affecting phosphate removal from aqueous solutions by ion exchange were investigated – contact time and temperature, initial pH, initial phosphate concentration and resin dosage, and the presence of other ions. The best phosphate removal (99%) from 100 mg-P/L initial solution was observed at pH 10 and 25 °C after 3 hours of contact time. No negative phosphate removal results were obtained from phosphate solutions containing sulfate, nitrate and ammonium ions; i.e., resembling real wastewater. Desorption (with NaOH or NaCl) and recovery (with CaO) studies of phosphate sorbed by resin were also carried out, as well as thermodynamic investigations. The proportional desorbability of phosphate from the resin with NaCl was 85.6%. The recovery efficiency of phosphate was 79.4%. The sorption process was spontaneous and endothermic. The ion exchange mechanism was determined using different internal and external diffusion models. The mechanism controlling the removal of phosphate from aqueous solution is both internal and external diffusion. Application of the Langmuir and Freundlich isotherm models showed that the experimental results fit well with the Freundlich model. HIGHLIGHTS The danger of phosphate in terms of water pollution.; Selective and high phosphate removal using Lewatit MonoPlus M 600.; Discussion of the mechanisms of phosphate removal.; Desorption of phosphate with NaCl is easy.;